Dead of winter - Coates, Darcy (Poisoned Pen Press, 2023)
"From bestselling author Darcy Coates comes Dead of Winter, a remote cabin in the snowy wilderness thriller that will teach you to trust no one. There are eight strangers. One killer. Nowhere left to run. When Christa joins a tour group heading deep into the snowy expanse of the Rocky Mountains, she's hopeful this will be her chance to put the ghosts of her past to rest. But when a bitterly cold snowstorm sweeps the region, the small group is forced to take shelter in an abandoned hunting cabin. Despite the uncomfortably claustrophobic quarters and rapidly dropping temperature, Christa believes they'll be safe as they wait out the storm. She couldn't be more wrong. Deep in the night, their tour guide goes missing ... only to be discovered the following morning, his severed head impaled on a tree outside the cabin. Terrified, and completely isolated by the storm, Christa finds herself trapped with eight total strangers. One of them kills for sport ... and they're far from finished. As the storm grows more dangerous and the number of survivors dwindles one by one, Christa must decide who she can trust before this frozen mountain becomes her tomb. Don't have enough scary books on your shelves?"--